Early HIV treatment and labour outcomes: a case study of mining workers in South Africa - French, Declan; Brink, Jonathan; Bärnighausen, Till (Health economics, 2019)
This study examines whether labour outcomes of HIV-infected workers treated with antiretrovirals are associated with the stage of the disease when commencing therapy. We use data on employment separation and absenteeism from the workplace health programme of South Africa's largest coal mining company over the period of January 2009 to March 2017 in a Cox proportional hazards model. When treatment was initiated at a CD4+ T cell count above 350 cells/μl, the risk of separating from the company was 37% lower and the risk of absence was 20%t lower than initiating at a CD4 count below 200 cells/μl, and these differences persist over time. Also, we find that workers initiating antiretroviral therapy at CD4 ≥ 350 have an 8% lower risk of absence prior to treatment. Although many companies and the South African government have adopted universal test-and-treat policies aiming to initiate all HIV-infected people as early as possible, most HIV patients still start treatment late in the disease course when their CD4 counts have fallen to low levels. Our results indicate early HIV detection and treatment could have large productivity gains.
First published: 21 October 2018
Gesehen am 04.04.2019